Blood pressure management protocol based on transtheoretical model effectiveness on self- care: A systematic review - Habibeh Barzegar; Sheida Sodagar; Mohammadreza Seirafi; Mostafa Farahbakhsh; Touraj Hashemi (Tabriz University of Medical Sciences, 2024)
Background: Hypertension is a prevalent medical condition associated with cardiovascular and kidney diseases, leading to premature death and disability. Despite medication use, hypertension continues to rise due to unhealthy lifestyles. Self-care strategies play crucial roles in effectively treating hypertension. We aimed to evaluate the effectiveness of interventions based on the transtheoretical model (TTM) in improving self-care, self-efficacy, and health-related quality of life (HRQOL) in hypertensive adults. Methods: A comprehensive search was performed in multiple databases using appropriate search strategies. Two independent reviewers screened articles, and assessed their adherence to the inclusion and exclusion criteria. The risk of bias in randomized controlled trials was assessed by the Cochrane Collaboration tool and quasi-experimental studies using the Joanna Briggs Institute (JBI) Critical Appraisal Checklist for Quasi-Experimental Studies. Results: The review included 24 studies with a total of 6553 participants. Most interventions aimed to encourage a healthier lifestyle and improve diet and physical activity. The message was delivered through various methods such as slide/tape messages, individual education/counseling sessions, telephone-delivered interventions, and multimedia training software based on the TTM. Control groups received physician visits or attended lifestyle lectures but did not receive specific behavior change programs like the intervention groups. Conclusion: Our results indicated that the TTM and stage of change model can be an appropriate framework for delivering educational messages to patients.